Should acupuncture, biofeedback, massage, Qi gong, relaxation therapy, device-guided breathing, yoga and tai chi be used to reduce blood pressure?: Recommendations based on high-quality systematic reviews. (February 2019) - Niu, Jian-fei; Zhao, Xiao-feng; Hu, Han-tong; Wang, Jia-jie; Liu, Yan-ling; Lu, De-hua
Abstract: Background: This review aims to rate the quality of evidence and the strength of recommendations in high-quality systematic reviews of non-drug therapies. Hypertensive patients who are resistant or non-adherent to antihypertensive drugs may be easier to manage if they choose alternative non-drug therapies for hypertension, based on this review. Methods: P: Adults (>18 years), except pregnant women, with essential hypertension.I: Cupping, moxibustion, acupuncture, acupoint stimulation, yoga, meditation, tai chi, Qi gong, Chinese massage, massage, spinal manipulation, biofeedback, device-guided breathing therapy, aromatherapy, music therapy, and relaxation approaches.C: 1. No treatment. 2. Sham therapy. 3. Conventional treatment, including antihypertensive drugs and lifestyle modification (e.g., exercise).O: 1. Change in the incidence of cardiovascular death. 2. Change in the incidence of myocardial infarction. 3. Change in the incidence of stroke. 4. Change in blood pressure (BP). 5. Efficacy rate of BP lowering. 6. Adverse effects (review specific).S: Systematic reviews of randomized controlled trials, including meta-analyses and assessments of the methodological quality/risk of bias. Information sources: Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Cochrane library, PubMed, Web of Science, China National Knowledge Infrastructure, and Chinese Scientific Journal Database were searched. The bibliographies of the included articles were also searched for relevant systematic reviews. GRADE criteria were used to rate the quality of evidence in systematic reviews considering 6 factors, including risk of bias. Results: This review ultimately included 13 systematic reviews of 14 non-drug therapies (acupuncture, wet cupping, Baduanjin, blood letting, auricular acupuncture, music, massage, Qi gong, moxibustion, relaxation therapies, biofeedback, device-guided breathing, yoga and tai chi) based on the inclusion criteria. The quality of evidence was generally low, and weak recommendations were given for most therapies except massage and acupuncture plus antihypertensive drug. Based on the analyzed evidence, massage and acupuncture plus antihypertensive drug could benefit people who want to lower their BP and do not have contraindications for massage and acupuncture plus antihypertensive drug. Discussion/Strength: The GRADE approach makes this review a unique reference for people who are considering the grade of quality of evidence in systematic reviews, the balance of desirable and undesirable consequences and the strength of recommendations to decide which intervention should be used to reduce BP. Limitations: Many non-drug therapies were excluded due to the low methodological quality of their systematic reviews, and only 14 therapies were evaluated in this review. As no patient-important outcomes were reviewed, surrogate outcomes were used to rate the strength of recommendations. This approach may cause a decrease in evidence quality according to GRADE, but we argue that this is appropriate in the context of this review.